Buoyancy‐motivated dissipative free convection flow of Walters‐B fluid along a stretching sheet under the Soret effect and Lorentz force influence - Basha, Hussain; Ballem, Sreenivasulu; Reddy, Gudala Janardhana; Holla, Harish; Sheremet, Mikhail A. (Heat transfer)
A two-dimensional numerical model has been framed to investigate the effect of buoyancy forces on magnetized free convective Walters-B fluid flow over a stretching sheet with Soret effect, heat radiation, thermal source/sink, and viscous dissipation. The current physical model is developed based on the stretching sheet geometry. The impact of Lorentz force on the nonlinear system is investigated and considered in the velocity equation. The influence of thermal radiation, heat source/sink, viscous dissipation, and Joule heating is considered in the energy equation. The effect of Soret parameter and chemical reaction on mass transfer is accounted in the concentration equation. The current physical model is governed by the highly coupled nonlinear system of partial differential equations. Owing to the inadequacy in the analytical techniques, the obtained governing equations are solved by using the bvp4c Matlab function via similarity transformations approach. Numerical computations are performed for the varying values of physical parameters, which are expressed in terms of tables and graphs. Magnifying viscoelastic parameter decays the velocity profile and enhances the thermal and concentration fields. Enhancing free convection parameters diminishe the velocity fields and magnifies the thermal profile. Thermal field magnifies with enhancing thermal radiation parameter and Eckert number. Enhancing the Soret number raises the concentration field. Also, the bvp4c Matlab function adequately simplifies the highly nonlinear coupled system of equations occurring in nature. The present similarity solutions presented in this paper coincides with previously published results in the literature.